DEVELOPMENT OF BLENDED LEARNING ON ENGLISH LEARNING OUTCOMES IN PJKR STUDY PROGRAM - Siregar, Epi Supriyani; Hariati, Puji; Nasution, Alwi Fahruzy; Daulay, Dicky Edwar; Rahman, Arief (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The study aims to determine the development of blended learning based on the results of learning English in the PJKR study program. The method used in this research is quasi-experimental. The quasi-experimental method is different from the actual experiment. In the quasi-experimental method, there is a control group. The sampling technique used in this research is cluster sampling, also called group sampling. Data collection is the most important part of research. Effective and complete data determine the quality of the researchers. In this study, the researchers used the learning achievement test technique, test, observation, and documentation. Based on the results of the research that had been done, the size of the concentration and distribution of the pretest result data for the experimental group were: the largest score was 75 and the smallest score was 36, the mean (mean) was 51.67, the median was 52, the mode was 40.5 and the standard deviation was 11.91. While the post-test data results, the highest score was 91 and the lowest score was 45, the mean (mean) was 72.8, the median was 76.9, the mode was 77.6, and the standard deviation was 15.58. So, the objectives to be achieved in the learning design have been implemented, and the blended learning model is able to influence student learning outcomes in English.